Contextualising Curriculum Design and Recontextualising Its Implementation: The Case of Climate Change Education for Southern African Transfrontier Conservation Area Practitioners - Mutizwa Mukute; Tichaona Pesanayi (Environmental Association of Southern Africa, 2014)
This paper discusses how the climate change education needs of park managers, ecologists, and community development officers in Southern African Development Community (SADC) Transfrontier Conservation Areas (TFCAs) were established through contextual profiling. It subsequently analyses how a curriculum that was designed in response to a contextual profiling process was recontextualised during implementation by the SADC Regional Environmental Education Programme (REEP), with support from German Federal Enterprise for International Cooperation (GIZ). The paper's purpose is to trace the trajectory of contextualised curriculum development and implementation with a view to identifying how the twin concepts of contextual profiling and recontextualisation were utilised and lessons were learnt. The paper has potential value for educators/trainers interested in increasing the relevance of protected area workplace learning and its congruence to learners' realities.